2019
DOI: 10.1016/j.neubiorev.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes related to the hypothalamic-pituitary-adrenal axis and antidepressant response – Systematic review

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In our series, the only factor that entered the model was USN, but the exclusion of patients with a relevant history of pre-depression probably ruled out some of the potential non-responder cases (65). A recent study found that in major depressive disorder and in persistent depressive disorder, specific single nucleotide polymorphisms and haplotypes in genes related to the corticotrophin-releasing hormone (CRHBP, CRHR1) and melanocortins (POMC) predicted the non-responder status (66). Therefore, it is also important to perform these studies in PSD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the only factor that entered the model was USN, but the exclusion of patients with a relevant history of pre-depression probably ruled out some of the potential non-responder cases (65). A recent study found that in major depressive disorder and in persistent depressive disorder, specific single nucleotide polymorphisms and haplotypes in genes related to the corticotrophin-releasing hormone (CRHBP, CRHR1) and melanocortins (POMC) predicted the non-responder status (66). Therefore, it is also important to perform these studies in PSD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism is based on a dysfunction in the hypothalamic-pituitary-adrenal (HPA) axis. Research found that a disturbance might be secondary to gene polymorphism ( 49 ), exposure to maternal depression in childhood ( 50 ) or experience of early life stress ( 51 ) ( Figure 1 ). In general, studies share a view that depressive patients presented hypercortisolemia ( 52 54 ), unless they had an atypical depression ( 55 ).…”
Section: Mechanism Of Impaired Cognition In Depressionmentioning
confidence: 99%
“…Moreover, normalization of HPA axis activity in patients with depressive disorders has shown improved clinical outcomes (Min et al, 2012 ). In some animal models of depression, antidepressants, anxiolytics, and mood stabilizers have been shown to reduce the overall responsiveness of the HPA axis (Fernandez et al, 2013 ; Valvassori et al, 2017 ; Fischer et al, 2019 ). Hence, it is inferred that aberrant activation of the HPA axis may play a possible role in the pathophysiology of depression.…”
Section: Introductionmentioning
confidence: 99%